Cx43-Associated Secretome and Interactome Reveal Synergistic Mechanisms for Glioma Migration and MMP3 Activation - Aftab, Qurratulain; Mesnil, Marc; Ojefua, Emmanuel; Poole, Alisha; Noordenbos, Jenna; Strale, Pierre-Olivier; Sitko, Chris; Le, Caitlin; Stoynov, Nikolay; Foster, Leonard J.; Sin, Wun-Chey; Naus, Christian C.; et al. (Frontiers in Neuroscience, 2019)
Extracellular matrix remodeling, degradation and glioma cell motility are critical aspects of glioblastoma multiforme (GBM). Despite being a rich source of potential biomarkers and targets for therapeutic advance, the dynamic changes occurring within the extracellular environment that are specific to GBM motility have yet to be fully resolved. The gap junction protein connexin43 (Cx43) increases glioma migration and invasion in a variety of in vitro and in vivo models. In this study, the upregulation of Cx43 in C6 glioma cells induced morphological changes and the secretion of proteins associated with cell motility. Demonstrating the selective engagement of ECM remodelling networks, secretome analysis revealed the near-binary increase of osteopontin and matrix metalloproteinase-3 (MMP3), with gelatinase and NFF-3 assays confirming the proteolytic activities. Informatic analysis of interactome and secretome downstream of Cx43 identify networks of glioma motility that appear to be synergistically engaged. The data presented here implicate ECM remodelling and matrikine signals downstream of Cx43/MMP3/osteopontin and ARK1B10 inhibition as possible avenues to inhibit GBM.